1982
DOI: 10.1111/j.0954-6820.1982.tb01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptokinase or Heparin in the Treatment of Deep Vein Thrombosis

Abstract: In a previous study on 42 patients with acute deep vein thrombosis, randomly allocated to treatment with streptokinase or heparin, we found that 71.4 % of the streptokinase-treated patients achieved phlebographically significant thrombolysis as compared to 23.8% in the heparin group. These patients have been reevaluated after a mean observation period of 64 years. Seven patients had died and there were no other drop-outs. Thus, 35 patients were subjected to the follow-up study consisting of phlebography and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…Although several studies have compared systemically delivered thrombolytics with anticoagulation alone for DVT, few evaluated the occurrence of PTS as a primary outcome. [93][94][95][96] Although this limited number of studies suggested a reduction in PTS, the risk of major bleeding was greater with systemic thrombolysis than with anticoagulation alone or CDT. 96,97 Moreover, there is a nontrivial failure rate of systemic thrombolysis resulting, in part, from the poor concentration and penetration of thrombolytics within the thrombus itself.…”
Section: Thrombolysis/endovascular Therapies To Prevent Ptsmentioning
confidence: 99%
“…Although several studies have compared systemically delivered thrombolytics with anticoagulation alone for DVT, few evaluated the occurrence of PTS as a primary outcome. [93][94][95][96] Although this limited number of studies suggested a reduction in PTS, the risk of major bleeding was greater with systemic thrombolysis than with anticoagulation alone or CDT. 96,97 Moreover, there is a nontrivial failure rate of systemic thrombolysis resulting, in part, from the poor concentration and penetration of thrombolytics within the thrombus itself.…”
Section: Thrombolysis/endovascular Therapies To Prevent Ptsmentioning
confidence: 99%
“…As discussed above, recurrent VTE is associated with the development of PTS. Finally, small randomized trials have observed the use of contemporary surgical venous thrombectomy and systemic thrombolysis to be associated with reduced PTS rates compared with anticoagulation alone, but at the price of greater invasiveness and more complications, including major bleeding (36)(37)(38)(39)(40)(41)(42).…”
Section: Noninterventional Methods To Prevent Ptsmentioning
confidence: 99%
“…Although evidence of partial clot removal efficacy was demonstrated and two small, long-term follow-up studies with major methodological limitations did suggest a reduction in PTS, major bleeding was increased by 3-4 times over anticoagulation alone. [13][14][15] Therefore, systemic thrombolytic therapy is not recommended for the treatment of DVT. 3 CDT refers to the direct intrathrombus administration of a fibrinolytic drug via a catheter or device embedded within the thrombus using imaging guidance.…”
Section: Acute Dvtmentioning
confidence: 99%